Analisis Pengaruh Penyekatan Kanal Terhadap Muka Air Tanah Dan Pemetaan Risiko Kebakaran - Muhammad Kusairi; Sigit Sutikno; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Tanjung Leban Village is a village whose majority consists of deep peatlands, reaching depths to dozens of meters. The condition of the ground water level far from the surface of the peat soil causes the peatlands to be prone to fire. Government Regulation No.57 of 2016 states that the height of the ground water level on peatlands must be maintained so as not to fall less than 40 cm below the surface of the peat. The peat restoration agency established a canal blocking program to raise and maintain the ground water table 40 cm from the ground. So how is the influence of canal blocking on ground water level and mapping the level of fire risk. Groundwater level data obtained in the field from the height of measurements using a float on a monitoring well. The analysis shows that water flow tends to flow from the land into the canal, because the water level in the land is higher than the water level in the canal. The installation of the canal raises the groundwater level 60.5 cm and affects the water level to a distance of 476 m from the canal, after that the ground water level can only be increased by rainfall and water distribution from the concession area. The highest fire risk level was in February with a percentage of 100%, while the lowest risk level was in January with a safe percentage of 1.74%, standby 1.67% and danger or hazard-prone to 96.58%. Keyword: canal blocking, ground water level, fire risk level